The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1039/d2ce00972b
|View full text |Cite
|
Sign up to set email alerts
|

Reversible on/off conformational switching of pentafluorobenzoyl amide triggered by acid vapor and sublimation

Abstract: Most conformational molecular switches based on amide skeleton had been limited in their use in a solution. We developed a molecular switch with an amide skeleton, which is applicable without...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(41 reference statements)
1
0
0
Order By: Relevance
“…Upon analysis, we observed that 7 exhibited a predominant cis conformation (CD 2 Cl 2 at 216 K, 98%), as expected from the effect of the bulky N -substituents. , The cis conformation was also confirmed in the crystal structure (Figure and SI Section 1). Comparison of the conformational preferences of 5a and 7 suggests that hydrogenation and dehydration can serve as a molecular switch, analogous to the amide-based molecular switch demonstrated in our previous work. …”
Section: Resultssupporting
confidence: 54%
“…Upon analysis, we observed that 7 exhibited a predominant cis conformation (CD 2 Cl 2 at 216 K, 98%), as expected from the effect of the bulky N -substituents. , The cis conformation was also confirmed in the crystal structure (Figure and SI Section 1). Comparison of the conformational preferences of 5a and 7 suggests that hydrogenation and dehydration can serve as a molecular switch, analogous to the amide-based molecular switch demonstrated in our previous work. …”
Section: Resultssupporting
confidence: 54%